2016
DOI: 10.2217/epi-2016-0074
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse, Promoter Methylation of Leukocyte NR3C1 and the Potential Modifying Effect of Emotional Support

Abstract: Aim:To investigate childhood abuse victimization in relation to adult DNA methylation levels in a novel region of NR3C1, with emotional support as a possible modifier. Materials & methods: 295 participants from the Black Women's Health Study. Multivariable linear regression models were used to compute differences in mean percent methylation levels. Results: Women reporting childhood abuse victimization exhibited higher mean NR3C1 methylation levels than nonabused women, with a clear dose-response relationship.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 53 publications
0
32
1
2
Order By: Relevance
“…This study had a number of limitations, the major one being the assessment of NR3C1 methylation using DNA from a peripheral tissue (saliva DNA). Still, previous studies on NR3C1 exon 1F methylation and early trauma have generated similar results by utilizing DNA from brain 10 , 11 , saliva 12 , 18 , 28 , and whole blood leukocytes 13 , 14 , 16 , 22 . In addition, the cross-sectional design prevented the study of the timing of methylation in relation to the timing of the stressful events and of the onset of symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…This study had a number of limitations, the major one being the assessment of NR3C1 methylation using DNA from a peripheral tissue (saliva DNA). Still, previous studies on NR3C1 exon 1F methylation and early trauma have generated similar results by utilizing DNA from brain 10 , 11 , saliva 12 , 18 , 28 , and whole blood leukocytes 13 , 14 , 16 , 22 . In addition, the cross-sectional design prevented the study of the timing of methylation in relation to the timing of the stressful events and of the onset of symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, our study evaluated associations with telomere length as a marker of accelerated aging, but other markers including DNA methylation, are important and their examination will enhance our understanding of the biological impact of abuse experienced in early-life [ 68 ]. Our group has previously shown that childhood abuse victimization was associated with hypermethlation in NR3C1 [ 39 ]. Ongoing analyses within the Study on Psychosocial Stress, Spirituality, and Health are examining the impact of abuse and other stressful life experiences on DNA methylation within candidate genes in the stress pathway ( HSD11B1 , HSD11B2 , NR3C1 , FKBP5 ) and in epigenome-wide association studies.…”
Section: Discussionmentioning
confidence: 99%
“…We assigned respondents 1 point for each report of a physical abuse item that occurred >4 times, except for “choked or burned” or “seriously harmed someone I loved” where we assigned 1 point if they occurred 1 to 3 times and 2 points if they occurred 4 times. The resulting scores were categorized using the following groupings: no abuse (0), mild abuse (1), moderate abuse (2), severe abuse (≥3) [ 39 ]. We evaluated the impact of physical abuse in childhood or adolescence separately, and cross-classified yes/no indicators of physical abuse in childhood and adolescence to generate a four-level variable that indicated no physical abuse, physical abuse in childhood only, adolescence only, or childhood and adolescence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the few studies in healthy adults with a history of childhood adversity are especially valuable for detecting whether methylation in NR3C1 is responsive to early life adversity. In such adults, greater childhood adversity was associated with higher methylation in NR3C1 (32, 33). These findings suggest that early life adversity might pose a significant independent risk factor for NR3C1 methylation.…”
Section: Introductionmentioning
confidence: 98%